2013
DOI: 10.1007/s00264-013-2037-8
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced oxidative stress promotes autophagy through mitochondrial damage in rat notochordal cells

Abstract: Purpose Diabetes mellitus is associated with an increased risk of intervertebral disc degeneration (IDD). Reactive oxygen species (ROS), oxidative stressors, play a key role in autophagy of diabetes-associated diseases. Mitochondria are known to be the main source of endogenous ROS in most mammalian cell types. The authors therefore conducted the following study to evaluate the effects of high glucose concentrations on the induction of oxidative stress and autophagy through mitochondrial damage in rat notochor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 26 publications
1
74
0
1
Order By: Relevance
“…Untreated DM can cause many complications, such as cardiovascular disease, chronic renal failure, retinopathy and neuropathy [2]. DM is also considered to be an important aetiological factor in intervertebral disc degeneration [3][4][5]. Previous studies have reported a higher incidence of degenerative disc diseases in patients with DM than in the patients without DM [6].…”
Section: Introductionmentioning
confidence: 98%
“…Untreated DM can cause many complications, such as cardiovascular disease, chronic renal failure, retinopathy and neuropathy [2]. DM is also considered to be an important aetiological factor in intervertebral disc degeneration [3][4][5]. Previous studies have reported a higher incidence of degenerative disc diseases in patients with DM than in the patients without DM [6].…”
Section: Introductionmentioning
confidence: 98%
“…Dear Editor, Recently, we read with great interest the article by Park et al [1], who demonstrated that high glucose could impair the transmembrane potential, increase production of reactive oxygen species and activate autophagy in rat notochordal cells. The result of this research is consistent with our previous study, which indicated that autophagy was increased in rats with type I diabetes mellitus [2].…”
mentioning
confidence: 99%
“…24 Autophagy can also be induced by high glucose levels in various cell types, partly through hyperglycemia-mediated reactive oxygen species production, and has protective effects in vitro. [47][48][49] In fact, activation of MTOR was associated with an accelerated glomerular injury of DN-or puromycin models potentially suggesting an involvement of autophagy in these disease models 50,51 Nevertheless, the direct role of autophagy in diabetic nephropathy is not fully understood. Thus, the objective of this study was to investigate the precise involvement of podocyte and endothelial autophagy in the pathogenesis of diabetic nephropathy in vivo.…”
Section: Introductionmentioning
confidence: 99%